High performance fibers: a review on current state of art and future challenges - Avci, Huseyin; Hassanin, Ahmed; Hamouda, Tamer; Kılıç, Ali (Eskisehir Osmangazi Universitesi Muhendislik ve Mimarlik Fakultesi Dergisi, 2019)
Improving properties of polymeric and non-polymeric fibers, for example mechanical, dimensional stability, thermal degradation, and etc. with understanding a recent theoretical investigation on the solid mechanism of single crystal growth leads to obtain fiber-based products with unusual characteristics. Similarly, high performance fibers are important engineering products and widely used due to their outstanding mechanical property along with dimensional stability. They have found extensive use as fiber reinforcement and can be utilized in many applications such as cords, ropes, performance fabrics, electronic packaging, sports equipment and fiber optics (Hearle, 2001; Kerr, Chawla and Chawla, 2005). It is well known that the highest tenacity and elastic moduli reported for such fibers are still much lower than their theoretical values. An extensive open gap between theoretical values and practical results encourage scientists to workand improve the mechanical properties. On the other hand, due to their nonconventional chemistry and instrumentation, many researches have been concentrated on reducing its production costs. Additionally, there is no single fiber chemistry that can withstand all sort of end-use conditions. The objective of this review paper is to provide a critical andconstructive analysis on current state of art high performance fiber production and modification techniques. Current problems and novel solutions were emphasized separately.
Keywords: Composite material; Yüksek performans; lifler; organik; inorganik; gelecek beklentileri; Polymers and Plastics; Fiber Surface Modification; Reinforced Polymers; organic; inorganic; Recycling Technologies for Carbon Fiber Composites; Materials Science; Natural Fibers; FOS: Mechanical engineering; fibers; Engineering; Composite Materials and Structures; Mechanical Properties; Current (fluid); Nanotechnology; Malzeme Üretim Teknolojileri; Fiber; future directions; FOS: Nanotechnology; Mechanical Engineering; Engineering physics; Engineering (General). Civil engineering (General); Computer science; Mechanical engineering; Materials science; High performance; fibers; organic; inorganic; future directions; Mechanics of Materials; Electrical engineering; Physical Sciences; Natural Fiber Reinforced Polymer Composites; Material Production Technologies; TA1-2040; Fiber-Reinforced Composites; high performance